Materials testing laboratory of the Public works Misitry of Buenos Aires Province, national pioneer in the management of science and technology - Delgado, Arnoldo Oscar (2013)
Fil: Delgado, Arnoldo Oscar. Comisión de Investigaciones Científicas de la Provincia de Buenos Aires. Laboratorio de Investigaciones del Territorio y el Ambiente; Argentina.